Qualifying with Different Types of Quizzes in an Online EFL Course: Influences on Perceived Learning and Academic Achievement - Çakıroğlu, Ünal; Saylan, Esin; Çevik, İsak; Özkan, Adem (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
This quasi-experimental study explored how different online exam types differentiate learners’ academic achievement and perceived learning. The participants comprised 95 undergraduate students enrolled in an English course at a Turkish university in three groups, each taking a different type of quiz: with multiple-choice, open-ended, and mixed type questions. The results indicated that the academic achievement of the students in multiple-choice and open-ended groups increased and that quiz results improved the most for the multiple-choice group relative to the other groups. The study found a moderate level of significant relationship between cognitive and affective perceived learning and multiple-choice quiz scores. In addition, the study found a weak level of significant relationship between cognitive and affective perceived learning and mixed-design quiz scores, and between cognitive learning and the academic achievement scores of the mixed-design group. Semi-structured online interviews undertaken to further explain the quantitative data displayed positive influences of the different types of quizzes in terms of study behaviors and satisfaction. The findings of this study are expected to shed light for practitioners aiming to use different online assessment types.